Pembuatan Bioetanol Dari Biji Salak (Salacca edulis) Melalui Fermentasi - Anggraeni, Yuni; Supriadi, Supriadi; Mustapa, Kasmudin (Universitas Tadulako, 2017)
Salak seed is a waste of salak fruit that contains a high carbohydrate, therefore it can be used as an alternative raw material for the production of bioethanol. The study aims to determine the optimum time of fermentation to produce the highest content of bioethanol and to determine the weight ratio of the yeast and the substrate that produce the highest content of bioethanol. Variations of yeast mass used was 2, 4, and 6 grams and fermentation time were 24, 48, 72, 96, 120, and 144 hours. The analysis showed that the highest content of bioethanol produced was 6 grams of the yeast mass, the fermentation time was 48 hours and the weight ratio of yeast to the substrate was 6: 10 that obtained 11.2%.